2017
DOI: 10.15698/mic2017.04.568
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of yeast [PSI+] prion formation is increased during chronological ageing

Abstract: Ageing involves a time-dependent decline in a variety of intracellular mechanisms and is associated with cellular senescence. This can be exacerbated by prion diseases which can occur in a sporadic manner, predominantly during the later stages of life. Prions are infectious, self-templating proteins responsible for several neurodegenerative diseases in mammals and several prion-forming proteins have been found in yeast. We show here that the frequency of formation of the yeast [PSI+] prion, which is the altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
1
18
3
Order By: Relevance
“…Importantly, curing had no effect on the survival rates of naïve [ psi - ] cells, indicating that neither the guanidine hydrochloride treatment nor other prions that may have been initially present in the cells are responsible for these observations ( Fig 1 , S1 Fig and S6 Fig ). In contrast with our findings, Speldewinde and Grant reported that cured cells had a shorter lifespan compared to [ PSI + ] cells [ 23 ]. It is important to note that these authors used five rounds of growth on guanidine hydrochloride-containing medium to cure cells [ 23 ], a harsh and selective treatment that could have unknown side-effects, as opposed to our gentler curing conditions sufficient to eliminate [ PSI + ] ( Fig 1C , S4 Fig and S5 Fig ), through two passages on guanidine hydrochloride-containing medium (see Materials and Methods section).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Importantly, curing had no effect on the survival rates of naïve [ psi - ] cells, indicating that neither the guanidine hydrochloride treatment nor other prions that may have been initially present in the cells are responsible for these observations ( Fig 1 , S1 Fig and S6 Fig ). In contrast with our findings, Speldewinde and Grant reported that cured cells had a shorter lifespan compared to [ PSI + ] cells [ 23 ]. It is important to note that these authors used five rounds of growth on guanidine hydrochloride-containing medium to cure cells [ 23 ], a harsh and selective treatment that could have unknown side-effects, as opposed to our gentler curing conditions sufficient to eliminate [ PSI + ] ( Fig 1C , S4 Fig and S5 Fig ), through two passages on guanidine hydrochloride-containing medium (see Materials and Methods section).…”
Section: Discussioncontrasting
confidence: 99%
“…A prolonged chronological lifespan allowing cells to survive longer under such conditions would be a major selective advantage for yeasts in the wild, which could explain the extraordinary conservation of the prion-forming ability of Sup35p over one billion years of fungal evolution [ 22 ]. In agreement with our own findings, Speldewinde and Grant recently reported that [ PSI + ] improves chronological lifespan and proposed this could be due to an increased autophagic flux [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…To which extent the [PSI + ] variants affect the proteome is however still unclear (Baudin-Baillieu et al, 2014;Chan et al, 2017). [PSI + ] has been shown to facilitate the phenotypic manifestation of hidden genetic variation (True and Lindquist, 2000;True et al, 2004;Tyedmers et al, 2008;Halfmann et al, 2012), and we and others have recently showed that [PSI + ] cells have a longer chronological lifespan (Speldewinde and Grant, 2017;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Viability assays were performed as previously described [50,51]. Briefly, colonies on SD agar medium (with or without ZnCl 2 ) were harvested in phosphate-buffered saline and incubated at 30°C for 30 minutes with 2 µM propidium iodide (Molecular Probes).…”
Section: Yeast Viability Assaysmentioning
confidence: 99%